QUALITY OF EDUCATIONAL ENVIRONMENT AT WAH MEDICAL COLLEGE: ASSESSMENT BY USING DUNDEE READY EDUCATIONAL ENVIRONMENT MEASURE - Mushtaq, Robina; Ansar, Ambreen; Bibi, Anwar; Ramzan, Musarat; Munir, Asif; Zaheer, Amna; Aslam, Anam; Ahmad, Afsa; Barlas, Aisha (Journal of Ayub Medical College Abbottabad, 2017)
Background: Educational environment not only has an impact on the students during the academic years but has its reflections throughout their medical career. The Dundee Ready Educational Environment Measure (DREEM) is an internationally accepted useful tool to analyse undergraduate educational environments in the health professionals. The purpose of this study was to assess how students, across all the five years in a private medical college, perceive their educational environment. Methods: It was a cross sectional study, which used the DREEM inventory at Wah Medical College over the course of 6 months (January-June 2015). All 500 students were included in the study. The fifty items DREEM inventory, having the maximum score of two hundred indicating ideal educational environment was used for data collection. Results: The questionnaire was completed by 400 undergraduate medical students (response rate 80%). The overall DREEM score was 122.63/200 (61.3%), indicating that the perception of the learning environment was more positive than negative. Among the highest scoring categories were students' participation in classes, relaxed atmosphere and confidence in passing the annual exams. However, many areas requiring improvement were also brought to attention. Conclusion: Overall, the student's perception of their learning environment at Wah Medical College was found to be positive. This study did bring to light some areas that could be improved upon. This should enable the faculty to adopt changes in their teaching methods to make the learning process more productive and enjoyable for future students. Keywords: Medical students; Perception; Educational environment; DREEM inventory